Erosion by a two-dimensional horizontal jet on a movable bed downstream of a fixed bed - Moncada, Alix; Aguirre Pe, Julián (Rev. Téc. Fac. Ing. Univ. Zulia)
In this paper the local scour produced on a loose material bed downstream of a fixed bed, due to a submerged horizontal jet of water issuing through a sluice opening, is analyzed. An experimental study of the phenomenon of scour is made. Experiments were carried out with two natural sand sizes for various sluice openings and jet velocities. The experiments were conducted in a glass-walled channel, 0,5 m wide and 0,5 m depth. The parameters that characterize the phenomenon of scour were identified based on the physical reasoning and dimensional analysis. Then, they were correlated through the development of empirical expressions, which allow to predict the characteristic lengths of the scour hale al the equilibrium stage. Moreover, some experimental results of the time variation of scour hole are presented. Evolution of .scour, as a function of time and position, until reaching an equilibrium condition, is obtained. Equations for time variation of maximum scour depth and the scour hole length are empirically obtained.